DEVELOPING WORDSMITH - Scott, Mike (International Journal of English Studies, 2008)
WordSmith Tools, since its launch in 1996, has had a rather unusual history and the aim of this paper is to record some of the chief influences on its development. The paper thus presents and discusses the history of WordSmith Tools and its predecessors going back to the early 1980s when processors were much slower, memory very limited and disk space expensive. It is structured around the discussion of certain key issues, principles and themes. These include: “on the fly” processing, corpus flexibility, language independence, user control aspects, the unpredictability of design needs, a move towards remote processes, modular construction principles, software production management, pattern-seeking and the development of new corpus linguistic terms.